2020
DOI: 10.1016/j.ajpc.2020.100090
|View full text |Cite|
|
Sign up to set email alerts
|

Prior cardiovascular risk and screening echocardiograms predict hospitalization and severity of coronavirus infection among elderly medicare patients

Abstract: Background The COVID-19 pandemic has disproportionally impacted the elderly. In the United States and Europe the mortality rate of elderly patients with COVID-19 is greater than 30%. Our aim is to determine predictors of COVID-19 related hospitalization and severity of disease among elderly Medicare patients in the United States. Methods We conducted a retrospective cohort study including elderly Medicare COVID-19 patients across eight states. We collected data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Therefore, the need for unique strategies to protect vulnerable groups such as the elderly is proving vital. Interestingly, assessing cardiovascular risk, comorbidities through Charlson comorbidity index, socioeconomic status, and echocardiographic measures, can predict the severity and mortality after SARS-CoV-2 infection [34]. On the contrary, other studies reported that male sex, hypertension, and smoking did not independently correlate with fatal outcomes [29].…”
Section: Hypertension and Diabetes Mellitusmentioning
confidence: 99%
“…Therefore, the need for unique strategies to protect vulnerable groups such as the elderly is proving vital. Interestingly, assessing cardiovascular risk, comorbidities through Charlson comorbidity index, socioeconomic status, and echocardiographic measures, can predict the severity and mortality after SARS-CoV-2 infection [34]. On the contrary, other studies reported that male sex, hypertension, and smoking did not independently correlate with fatal outcomes [29].…”
Section: Hypertension and Diabetes Mellitusmentioning
confidence: 99%
“… 27 From a management perspective, patients with COVID‐19 and age‐specific high NT‐proBNP on admission may need cardiac imaging even in the absence of history of Stage C HF. Dormant Stage B disease may place patients at higher risk, 28 and structural abnormalities combined with myocardial injury are associated with increased mortality. 15 Elevated NT‐proBNP in patients admitted with COVID‐19 with no known cardiac conditions may point to COVID‐19‐mediated cardiac complications, and therefore, these patients should be considered for cardiac imaging.…”
Section: Discussionmentioning
confidence: 99%
“…At 28 days, patients had a median of 18 hospital-free days (0-23), 28 ICU-free days (15-28), and 28 ventilator-free days (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In adjusted analyses, patients with high admission NT-proBNP spent fewer hospital-free, ICU-free, and ventilator-free days compared with those with low admission NT-proBNP, by 32%, 33%, and 33%, respectively (Table 3).…”
Section: N-terminal Pro-b-type Natriuretic Peptide and Healthcare Resources Utilizationmentioning
confidence: 99%
“…In general, the mortality rate of this virus is 3.4%, which is higher in the elderly and patients with underlying diseases compared with other patients ( Ghany et al, 2020 ). In this regard, this retrospective study analyzed biochemical parameters of COVID-19 patients both in survival and death groups, which may help to identify critical factors and provide appropriate clinical intervention early.…”
Section: Introductionmentioning
confidence: 99%